Sobre lesbianidade(s): o que pensam as juventudes? - Gonçalves Medeiros, Talita (2019)
The present study aimed to interrogate and understand the representations about lesbianity (s) produced by students of an agricultural school in the southern region of the state of Rio Grande do Sul. The research, guided by Lesbofeminist Cultural Studies, produced their data from "conversation wheels" supplemented by notes in the "field diary". From the analysis of the data, we can point out that the students have critical and conceptual visions and understandings about the lesbian (s). From the thematic one it was possible to understand that the "lesbianity (s) is crossed by the invisibility school-historical and when visible, anchors itself in representations mediated only by the violence.